2013
DOI: 10.1007/s11214-013-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Turbulence and the Role of Ion Instabilities

Abstract: Solar wind is probably the best laboratory to study turbulence in astrophysical plasmas. In addition to the presence of magnetic field, the differences with neutral fluid isotropic turbulence are: (i) weakness of collisional dissipation and (ii) presence of several characteristic space and time scales. In this paper we discuss observational properties of solar wind turbulence in a large range from the MHD to the electron scales. At MHD scales, within the inertial range, turbulence cascade of magnetic fluctuati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 271 publications
(228 citation statements)
references
References 205 publications
13
206
0
Order By: Relevance
“…The maximum of distributions of the P 1 slope are approximately −(1.6 to 1.7), and of the P 2 ∼ −(2.6 to 2.8). The average values of the slope of the low frequency range P 1 = −1.6 ± 0.2 are in a good agreement with the numerous experimental results of plasma and IMF parameters in SW obtained earlier (see the reviews [1,2] and references therein) and correspond approximately to the slope of the Kolmogorov model spectrum in the inertial range [12]. The average values of the slope at high-frequency range are equal P 2 = −2.9 ± 0.2.…”
Section: Introductionsupporting
confidence: 91%
“…The maximum of distributions of the P 1 slope are approximately −(1.6 to 1.7), and of the P 2 ∼ −(2.6 to 2.8). The average values of the slope of the low frequency range P 1 = −1.6 ± 0.2 are in a good agreement with the numerous experimental results of plasma and IMF parameters in SW obtained earlier (see the reviews [1,2] and references therein) and correspond approximately to the slope of the Kolmogorov model spectrum in the inertial range [12]. The average values of the slope at high-frequency range are equal P 2 = −2.9 ± 0.2.…”
Section: Introductionsupporting
confidence: 91%
“…It is therefore of interest to compare the scaling of the compressive fluctuations in the solar wind to that of the Alfvénic turbulence. While spectra of compressive fluctuations have long been measured in the solar wind (see reviews by Alexandrova et al 2013;Bruno & Carbone 2013), we have recently been able to investigate these with greater precision, to enable comparison to the Alfvénic turbulence. Chen et al (2011a) showed that the spectral indices of both δn and δ|B| are close to −5/3, similar to the magnetic field, rather than the velocity, which has a −3/2 spectral index.…”
Section: Spectra and Passivitymentioning
confidence: 99%
“…the nonGaussian nature of the fluctuations. Intermittency has been well studied in the solar wind for kρ i < 1 (see reviews by Alexandrova et al 2013;Bruno & Carbone 2013), where most quantities are seen to become increasingly non-Gaussian towards smaller scales, a well-known feature of turbulence. This is related to the turbulent energy being concentrated into a smaller fraction of the volume as the cascade proceeds to smaller scales, and results in the formation of energetic structures within the plasma.…”
Section: Intermittencymentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic Alfvén wave damping, in particular when resulting from nonlinear evolution, would be another option [15], in addition to causing anisotropy. Other suggestions favorise whistler wave damping [30] which, however, should be too weak for dissipating the input of mechanical turbulent energy.…”
Section: Inertial Range Spectrummentioning
confidence: 99%